PENETRASI PASAR PADA PRAKTIK B2C UNTUK RITEL - SUGIANTO, ADHIE PUTRA (Universitas Katolik Widya Mandala Surabaya, 2012)
Online transaction has some of use for consumer or retailer, but on the other side also has some of obstacles. Therefore, that obstacles must have the right solution and can do penetration to develop online transaction. For handle some of that obstacles, there has some efforts that could be do is give a support to government in terms of regulations setting for consumer interests are protected. For resources, retailer is feasible to enhance the ability of retailers resource, and also for network and infrastructure is need a support from government as well as businessman so the network can be more stable. For can do penetration, that retailers must do is give a lesson to business partners about online transaction operation, give a lesson to consumer about online transaction, and promote about onlne retailer’s web